The Need to Maintain the Quality of Naturally Pure Water of Sarayu River - Dr. Sarvesh Kumar Diwakar,; Prof. (Dr.) Udai Arvind, (International Journal of Scientific Research in Science and Technology, 2024)
Rivers are a link between human life and nature. All the ancient developed cities are situated on the banks of some river or the other ancient civilizations of India have developed on the banks of rivers. The river is helpful in both, flood and drought conditions, works to balance nature by absorbing the flood water inside itself and giving water to animals and humans during drought. In the present scenario, due to the increasing population of cities and the pollution arising from it, the water of rivers is getting polluted rapidly. Many rivers of the country are slowly disappearing and some rivers have water only during monsoon. Our country is slowly moving towards water crisis. To get out of this crisis, we all need a corrective change in behaviour along with scientific remedial system. The per capita availability of water has decreased significantly in the last 75 years. According to one figure, in 1951 the per capita was 5177 cubic meters but in the year 2011 only 1545 cubic meters of water is available per person. According to a study by the National Institute of Hydrology, India will have only 814 cubic meters of usable water per capita in 2025. When we studied the water of Sarayu river, it was found that all the parameters and heavy metals present in the water raised after monsoon are within the processed limit. When the properties of the water of Sarayu river were studied, surprising results came out. All the elements present in the water like calcium, magnesium, chloride, fluoride, alkalinity, nitrate ion, sulphate ion, arsenic and manganese etc. were within the required limits. Desirable limits of calcium, magnesium, chloride, alkalinity, nitrate ion, sulphate ion are 75 mg/l, 30 mg/l, 25 mg/l, 200 mg/l, 200 mg/l, respectively. The maximum values in pre-monsoon were found to be 38.47 mg/l, 26.24 mg/l, 15.9 mg/l, 192 mg/l, 0.20 mg/l and 20.10 mg/l respectively and in post-monsoon its maximum value was found to be 28.86 mg/l, 12.49 mg/l, 17.99 mg/l, 128 mg/l, 1.5 mg/l and 41.30 mg/l, respectively. The desirable limit of arsenic is 0.01, found to be 0.01 at some places in pre-monsoon but found to be nil in post-monsoon.
Keywords: Total Hardness; Sarayu River; Naturally Pure